2017
DOI: 10.22342/jme.9.1.4291.95-102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Media Scaffolding on Increasing Understanding of Students’ Geometry Concepts

Abstract: This study is a quasi-experimental research with pretest-posttest control group design, which aims to determine (1) the tendency of students in using various media scaffolding based on gender, and (2) effect of media scaffolding on increasing understanding of students' geometry concepts. Media scaffolding used this study is chart, props, and visual. The population was the fifth grade students of State Elementary School I Gunung Terang (total 40 students), Bandar Lampung, Indonesia of the academic year 2015-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
1
15
0
12
Order By: Relevance
“…Then, the researcher explained to the students that if line k and line l were dragged upward (while demonstrating it), then they would intersect in one point. The researcher's activity is similar to those suggested in (Eriana, Kartono, & Sugianto, 2019) and (Sutiarso et al, 2017) who found that using realia could effectively improve students' concept mastery in mathematics learning.…”
Section: Figure 3 Truncated Cone Illustrationsupporting
confidence: 75%
See 1 more Smart Citation
“…Then, the researcher explained to the students that if line k and line l were dragged upward (while demonstrating it), then they would intersect in one point. The researcher's activity is similar to those suggested in (Eriana, Kartono, & Sugianto, 2019) and (Sutiarso et al, 2017) who found that using realia could effectively improve students' concept mastery in mathematics learning.…”
Section: Figure 3 Truncated Cone Illustrationsupporting
confidence: 75%
“…Then, the students were asked to discuss it with their group members and finally communicate the result to the researcher. The construction of geometry concepts with concrete building models is an important part in understanding geometry (Dewi, Hakim, Setiawan, Adhisuwignjo, & Rohadi, 2018;Imswatama & Lukman, 2018;Sutiarso, Coesamin, & Nurhanurawati, 2017) revealed that the investigation of the properties of geometry and concrete shape is an important part in understanding geometry. The results of their research prove that the teaching media can help students understand concepts in geometry.…”
Section: Phase-4mentioning
confidence: 99%
“…In addition to the use of approaches in learning, learning media are also important. According to (Sutiarso, Coesamin, & Nurhanurawati, 2018), the use of instructional media, such as visual aids, charts, and visual media, is quite effective in increasing students' mathematical understanding. Comics can be an effective media or learning resource.…”
Section: Evaluation Phasementioning
confidence: 99%
“…Selanjutnya Sutiarso et al (2018) telah melakukan penelitian eksperimen semu dengan desain kelompok kontrol pretes-postes, yang bertujuan untuk menentukan pengaruh media scaffolding terhadap peningkatan pemahaman konsep geometri. Penelitian yang dilakukan di kelas 5 SDN 1 Gunung Terang Bandar Lampung dengan jumlah seluruhnya 40 peserta didik terbagi dalam 20 orang kelas kontrol dan 20 orang kelas eksperimen.…”
Section: •145unclassified